The Molecular Mechanism Underlying Pro-apoptotic Role of Hemocytes Specific Transcriptional Factor Lhx9 in Crassostrea hongkongensis - Zhou, Yingli; Mao, Fan; He, Zhiying; Li, Jun; Zhang, Yuehuan; Xiang, Zhiming; Xiao, Shu; Ma, Haitao; Zhang, Yang; Yu, Ziniu (Frontiers in Physiology, 2018)
Hemocytes are the central organ of immune defense against pathogens by means of inflammation, phagocytosis and encapsulation in mollusks. The well-functioning of the host immune system relies on the hemocytes’ task exertion and frequent renewal, but the underlying renewal mechanism remains elusive at the gene level. Here, we identified one transcription factor, LIM homeobox 9, in Crassostrea hongkongensis (ChLhx9) that could be involved in hemocyte apoptosis or renewal. ChLhx9 contains a homeodomain and two LIM domains. The expression profile of ChLhx9 showed that it was specific and had high expression in hemocytes, and it significantly increased under the bacterial challenge. RNA interference of ChLhx9 dramatically decreased the apoptosis rate of hemocytes when compared with a control group, which strongly implies its pro-apoptotic role in hemocytes. Furthermore, the genomic responses to the knockdown of ChLhx9 were examined through RNA-seq, which showed that multiple pathways associated with cell apoptosis, including the apoptosis pathway, hippo signal pathway and p53 signaling pathway, were significantly down-regulated. Meanwhile, seven of the key apoptotic genes were confirmed to be upregulated by ChLhx9, among which ChASPP1 (apoptosis stimulating protein of p53) was confirmed to induce hemocyte apoptosis strongly, which demonstrates that ChASPP1 was a downstream target mediated by ChLhx9 that caused apoptosis. In conclusion, tissue-specific transcription factor ChLhx9 induces hemocyte apoptosis through activating apoptotic genes or pathways, which could contribute to hemocyte renewal and immune defense in oysters.